Treatment of excessive urinary urgency and frequency by retention control training and desensitization; three case studies. - Espie, C (1985)
Three patients with lengthy histories of excessive urinary urgency and frequency were treated individually using behavioural techniques. After careful behavioural analysis revealed individual differences in presentation and compliance, personalized therapy programmes were constructed involving combinations of retention control training, in vivo desensitization and other anxiety-reduction techniques. The results suggest that retention training and desensitization can be successfully combined into an effective treatment package where one technique facilitates the administration of the other. The results are discussed with reference to the few documented case-reports available, and some guidelines for clinical practice and further investigation are suggested. © 1985.